PEMANFAATAN INSTRUMEN GAMELAN BALI PADA SCORING FILM PERSETERUAN - I Gede Diki Arinata; I Kadek Puriartha; Made Denny Chrisna (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Musical scoring in action films can be one of the media in strengthening narratives in action films. In addition, scoring music in action scenes can influence the mood and emotions that the director wants to manifest in each scene. The musical score is an important factor in shaping the emotion of each scene. Therefore, it is important for a sound engineer to design musical scoring in every action scene. In this report, the author as a sound engineer discusses how to use Balinese gamelan instruments in scoring music and the process of designing scoring music in action scenes in film with tittle Perseteruan or Enmity. Starting from the script breakdown part, tone design, instrument selection, sound effect selection until mixing and mastering process. The author also describes the use of Balinese gamelan instruments in the Perseteruan film. Balinese musical instruments have their own charm for the audience. The use of Balinese gamelan in the film score for the Perseteruan to support the background story in Bali. Exotic pentatonic tones make this Balinese gamelan instrument beuatifully elegant when it's played. The tones in Balinese gamelan are very identical to the atmosphere in Bali. Perseteruan film is an action film that depicts the enmity between two friends. Wayan and Bayu used to be best friends. But now that has changed after Wayan left prison and Bayu became one of the land mafia groups who wanted to sell Wayan's land. Wayan didn't agree because he wanted to build his own business on that land. In the end, Bayu tried any ways to get the land. From there, Wayan and Bayu's feud began.